2014
DOI: 10.5455/msm.2014.26.208-212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipoic Acid on Acrylamide Induced Testicular Damage

Abstract: Introduction:Acrylamide is very toxic to various organs and associated with significant increase of oxidative stress and depletion of antioxidants. Alpha-lipoic acid enhances cellular antioxidant defense capacity, thereby protecting cells from oxidative stress.Aim of the study:This study aimed to evaluate the protective role of alpha-lipoic acid on the oxidative damage induced by acrylamide in testicular and epididymal tissues.Material and methods:Forty adult male rats were divided into four groups (10 rats ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 31 publications
8
25
0
Order By: Relevance
“…In our study, treatment of rats with ACR increased MDA concentrations in both brain and testicular tissues compared to vehicle-treated rats. Consistent with our study, it was reported previously that treatment of rats with ACR significantly increases MDA levels in the nervous system 43,44,45 and the testes 36,46 . Treatment with MIN significantly decreased MDA concentrations in the brain and testicular tissues of ACR-treated rats indicating its antioxidant effects.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, treatment of rats with ACR increased MDA concentrations in both brain and testicular tissues compared to vehicle-treated rats. Consistent with our study, it was reported previously that treatment of rats with ACR significantly increases MDA levels in the nervous system 43,44,45 and the testes 36,46 . Treatment with MIN significantly decreased MDA concentrations in the brain and testicular tissues of ACR-treated rats indicating its antioxidant effects.…”
Section: Discussionsupporting
confidence: 93%
“…Both IGFBP‐3 and HSPA1 expression profiles in the present study were altered in the group administered with alpha lipoic acid in combination with ivermectin, where their expressions decreased than the group injected with ivermectin. As well, many studies reported that alpha lipoic acid treatment revealed the ameliorative effect on testicular pathology (Güleş & Eren, ; Lebda, Gad, & Gaafar, and Motawi et al., ). In the current study, histopathological section of testes in the group administered ALA with IVM showed mild testicular degeneration in some seminiferous tubules and nearly normal seminiferous tubules with spermatid and spermatozoa in the tubular lumen (Figure e).…”
Section: Discussionmentioning
confidence: 91%
“…Another study, conducted via AA administration of 2.5, 10, 50 mg kg −1 bw −1 for 14 days on 7‐week male rats, reported that AA dose‐dependently caused significant decrease in testosterone, progesterone, FSH levels compared to the control group in testis tissues ( Camacho et al, ). In a study, researchers administered 0.05% AA in drinking water and 1% lipoic acid in feed for 21 days to adult male rats and established that AA decreased the total testosterone, progesterone and GSH levels, increased estradiol and MDA levels and caused losses in several seminiferous tubules, giant cell formations and depletion of germinal cells (Lebda, Gad, & Gaafar, ).…”
Section: Discussionmentioning
confidence: 99%